Research on Access to Education and Educational Achievement in Barbados: A Review - Layne, Anthony (Institute of Social Economic Research, The University of the West Indies, Mona Campus, 1989)
This paper reviews the research that has been carried out in Barbados on access to education and educational achievement.
Keywords: Educational Research